Emerging roles and potential clinical applications of noncoding RNAs in hepatocellular carcinoma. (October 2021) - Cao, Pengbo; Jin, Qian; Feng, Lan; Li, Haibei; Qin, Geng; Zhou, Gangqiao
Abstract: Hepatocellular carcinoma(HCC) is one of the most common forms of cancer, and accounts for a high proportion of cancer-associated deaths. Growing evidences have demonstrated that non- protein-coding regions of the genome could give rise to transcripts, termed noncoding RNA (ncRNA), that form novel functional layers of the cellular activity. ncRNAs are implicated in different molecular mechanisms and functions at transcriptional, translational and post-translational levels. An increasing number of studies have demonstrated a complex array of molecular and cellular functions of ncRNAs in different stages of the HCC tumorigenesis, either in an oncogenic or tumor-suppressive manner. As a result, several pre-clinical studies have highlighted the great potentials of ncRNAs as novel biomarkers for cancer diagnosis or therapeutics in targeting HCC progression. In this review, we briefly described the characteristics of several representative ncRNAs and summarized the latest findings of their roles and mechanisms in the development of HCC, in order to better understand the cancer biology and their potential clinical applications in this malignancy.